Application of Murabahah Agreement in Griya Takeover Financing (Case Study at BSI Sub Branch Office Kuta) - Nur Halimah; Kurniawati; R. Agrosamdhyo (The International Conference on Education, Social Sciences and Technology (ICESST), 2023)
Griya Takeover Financing is one of the financing companies owned by BSI KCP Kuta to meet customers' financial needs. However, this financing often encounters problems in the takeover process. The aims of this study are: to find out the factors that lead to a murabahah contract in the financing of a takeover griya at BSI KCP Kuta and to find out the process of financing the griya takeover at BSI KCP Kuta. The research method used is a descriptive qualitative method with data collection techniques through observation, interviews, and documentation. The data analysis technique used is the Miles and Huberman model, which includes data collection, data reduction, data presentation, and data verification. data validity technique with the triangulation technique. The results of the study found: 1) There are factors that cause a murabaha contract to occur, namely the presence of the object of the contract; 2) The murabaha contract process by submitting asset documents to the consumer as a sign of consent qabul with the consumer. And financing for takeover houses that are free from usury in accordance with the Fatwa of the National Sharia Council, MUI No.04/DSN-MUI/IV/2000, dated April 1, 2000, conceming murabaha.; 3) The process of financing takeover housing includes BSI having the terms and benefits of financing takeover housing. To attract consumer, as well as with light installments, one of the benefits of takeover financing at BSI is that consumers still feel able to meet other needs.